2017
DOI: 10.1175/jcli-d-17-0174.1
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Synchronization of a Simple Stochastic Dynamical Model Capturing El Niño Diversity

Abstract: Recently, a simple stochastic dynamical model was developed that automatically captures the diversity and intermittency of El Niño–Southern Oscillation (ENSO) in nature, where state-dependent stochastic wind bursts and nonlinear advection of sea surface temperature (SST) are coupled to simple ocean–atmosphere processes that are otherwise deterministic, linear, and stable. In the present article, it is further shown that the model can reproduce qualitatively the ENSO synchronization (or phase locking) to the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

6
1

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…First, it has been shown that the climatological SST in the central-eastern Pacific cools in boreal fall and warms in spring as a result of the seasonal motion of the Intertropical Convergence Zone (ITCZ), which also modulates the strength of the upwelling and horizontal advection processes to influence the evolution of the SST anomalies 71 . Since the cool (warm) SSTs tend to coincide with decreased (increased) convective activity and upper cloud cover, a season-dependent damping term, which represents the cloud radiative feedback, is included for describing such a seasonal variation 44 . More specifically, two sinusoidal functions are utilized for parameterizing the otherwise constant α q , which appears as E q = α q T in (6).…”
Section: Seasonal Synchronizationmentioning
confidence: 99%
See 1 more Smart Citation
“…First, it has been shown that the climatological SST in the central-eastern Pacific cools in boreal fall and warms in spring as a result of the seasonal motion of the Intertropical Convergence Zone (ITCZ), which also modulates the strength of the upwelling and horizontal advection processes to influence the evolution of the SST anomalies 71 . Since the cool (warm) SSTs tend to coincide with decreased (increased) convective activity and upper cloud cover, a season-dependent damping term, which represents the cloud radiative feedback, is included for describing such a seasonal variation 44 . More specifically, two sinusoidal functions are utilized for parameterizing the otherwise constant α q , which appears as E q = α q T in (6).…”
Section: Seasonal Synchronizationmentioning
confidence: 99%
“…Specifically, WWBs can influence the ENSO development by stimulating eastward-propagating oceanic Kelvin waves, generating surface zonal currents and weakening the evaporation. In fact, many modeling works have been attempted to incorporate semistochastic parameterization for the WWBs 37,[40][41][42][43][44] and suggest that the coupled feedbacks between the interannual SST and the intraseasonal WWBs is sufficient to transfer a damped system to a semi-regular self-sustained oscillator. Likewise, in light of an intermediate coupled model (ICM), Lian et al 45 found that the WWBs are responsible for the existence of the irregularity and intensity of El Niño, whose specific characteristics depend on the timing of the WWBs relative to the phase of the recharge-discharge cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, in the centraleastern Pacific, the climatological SST cools in boreal fall and warms in spring as a result of the seasonal motion of the ITCZ, which also modulates the strength of the upwelling and horizontal advection processes to influence the evolution of the SST anomalies 41 . Since the cool (warm) SSTs tend to coincide with decreased (increased) convective activity and upper cloud cover, a season-dependent damping term, which represents the cloud radiative feedback, can account for this seasonal variation in a simple fashion 68 . Besides, the increased wind burst activity in winter as a direct response to the increased atmospheric intraseasonal variability such as the MJO is the main constitution of the seasonal cycle in the western Pacific 61,69 .…”
Section: Coupling Coefficients Between the Interannual Variables And ...mentioning
confidence: 99%
“…In particular, the model succeeds in capturing and predicting different super El Niño events [178], including both the directly formed (similar to 1997-1998) and delayed events (similar to 2014-2016). An improved version of the model is also able to recover the season synchronization [179]. The coupled model is as follows: Atmosphere…”
Section: A Coupled El Niño Model Capturing Observed El Niño Diversitymentioning
confidence: 99%